Geographical analysis of the reality of traffic accidents in Iraq for the year (2022) (Journal of the College of Basic Education, 2024)
The research aims to know the reality of traffic accidents in Iraq for the year (2022), with the exception of the Kurdistan region, by analyzing and classifying these accidents to reach knowledge of the spatial variation of the number of traffic accidents according to the governorates of Iraq and the reasons for their occurrence, and the research relied on the analytical approach and the quantitative approach in analyzing traffic accidents based on the latest data issued by the official authorities, as well as the use of the descriptive approach in classifying traffic accidents according to the place of accident, and the research reached a number of results, the most important of which are The collision accidents are the most frequent accidents according to the nature of the accident, which reached the highest in the province of Basra and the adult (1117) accident and by (17%), and that the province of Baghdad was one of the highest provinces incidence of traffic accidents according to the category of road, which was on highways with accidents amounting to (378) and (13%) of road accidents in Iraq. And that all traffic accidents had negative returns due to the material and human losses they caused, which was the factor of speed and non-compliance with traffic laws and regulations the main reason for their occurrence.